FLEKSIBILlTAS MUSIKAL SULUKAN GAYA SURAKARTA - Suyoto Suyoto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2004)
Wayang kulit is a representation of human life since the birth  until the death which is presented in patMt (musical concept or  musical atmosphere). Sulukan is an important medium and it is the  "soul" of the performance. Sulukan is divided into three: patMtan  (songs of the puppeteer accompanied by small gamelan ensemble),  senanon (the same genre as sulukan with specific musical effect), and  ada-ada (songs of the pupetteerto present tense atmospheres). Texts  used in sulukan are tembang gedhe (songs with long phrases),  tembang tengahan (songs with medium phrases), and tembang  macapat (songs with short phrases), those are different from other  songs. For that reason, the structure of sulukan is like that of  tembang in which rules are used. In sulukan there is kombangan  (songs with "vocal" expression rather than consonant) usually with the  word (long. " The kombangan becomes the special character of the  wayang kulit. Musically speaking, the kombangan is the "intermission"  between phrases. The texts relate to the social life and they are  contained in the texts of the sulukan; the contents of the sulukan are:  education of life, ethics, and mysticism in Javanese life.Keywords: Sulukan, fleksible musical, wayang kulit.